DYNAMIC RESPONSE AND STABILITY CONTROL OF BARGE PLATFORM FLOATING WIND TURBINE - WANG Bo; LI Chun; DING QinWei; ZHANG WanFu; ZHANG Li; LI ShuJun; LIU QingSong (Jixie qiangdu)
When TMD is used in the nacelle or tower of the floating wind turbine, its stability can be improved, but the fatigue load of the tower base is increased. In order to solve this problem, the ITI Barge platform is taken as the research object, TMD is arranged inside the platform for vibration damping control, and the dynamic model of the floating wind turbine is established to study the change law of the front-after and side-side displacement of the tower top with the TMD mass, damping and installation position. The multi-island genetic algorithm is used to obtain the optimal TMD parameters, and the effects of without TMD control, nacelle TMD control and platform TMD control on the dynamic response characteristics of floating wind turbine are compared and analyzed. The results show that the front-after and side-side displacements of the tower top change significantly with platform TMD parameters. When mass and damping of the platform TMD at the same location are large, the front-after and side-side displacements of the tower top decrease significantly. When mass and damping of the platform TMD remain unchanged, the front-after and side-side displacements of the tower top decrease gradually with the increase of the TMD location. Under the action of wind and wave, the effect of TMD on the dynamic response control of floating wind turbines under wind load is more obvious, but the control effect of each part is different. The side-side displacement of the tower top, the platform roll angle and the tower base roll bending moment control effect are the most significant. In addition, compared with the nacelle TMD control, the stability of the floating wind turbine is better when controlled by the platform TMD.